Karakteristik Perkembangan Anak Usia 6 Tahun di Kelas I Sekolah Dasar: Studi Observasional Kualitatif - Annisa Almeida; Fatin Adelya Putri; Kesi Kesi; Nurul Wardani Fadhilah; M.Torkis Lubis; Ramadhan Lubis (CV Edu Tech Jaya, 2026)
The age of 6 is a crucial period in a child's life as they begin to enter primary education, requiring physical, mental, social, and emotional readiness. This study aims to describe the developmental characteristics of 6 year-old children in grade 1 of elementary school and to identify factors that support this development. The topic discussed is how the developmental characteristics of 6 year-old children are seen from the physical, intellectual, social, and emotional aspects within the context of the home and school environments. This study uses a descriptive qualitative approach with direct observation methods on a 6 year-old child named Arsya Radipta, conducted in the school and home environments. To address this problem, systematic observations were made of the child's behavior, learning activities, and social interactions. The results of the study indicate that the child has normal physical development, good cognitive abilities, and relatively stable social and emotional development, although mild tantrums still occur in certain situations. Support from the family and a positive school environment play an important role in fostering independence and discipline. The conclusion of this study indicates that the optimal development of 6 year-old children is greatly influenced by cooperation and synergy between the family, school, and social environment.